PKM UMA SARI DI DESA SIDAN KABUPATEN GIANYAR BALI - Dewi, I Gusti Ayu Ratih Permata; Putri, Putu Yudha Asteria; Suariani, Luh (Universitas Kadiri, 2021)
Coconut shells or coconut shells may not be useful for most people, but craftsmen in Sidan Village, Gianyar District, Gianyar Regency, Bali can produce various kinds of tools for Hindu religious ceremonies. Coconut shell crafts are also widely used as souvenirs for tourists who come to Bali. The community service program is carried out in the trading business and the production of ceremonial tools from coconut shell